Relationship of Chronic Energy Deficiency, Birthweight and Exclusive Breastfeeding with Stunting in Kedungrejo Village, Pakis District, Malang - Endah Tri Maulina, Esthi; Radita Alma, Lucky; Nurrochmah, Siti (KnE Life Sciences, 2021)
n 2018, the average prevalence of stunting in Indonesia ranked sixth in the Asian region, at 36.4%. In the Java region, East Java ranked first with a stunting proportion of 32.81%. Malang is a district that has continued to experience an increase in the proportion of short nutritional status over the past three years: 22.9% in 2016, 28.3% in 2017 and 31.7% in 2018. Factors that affect stunting include income, education, economic status, number of family members, knowledge, exclusive breastfeeding, sanitation, clean water, health services, nutritional status of pregnant women, infections and birthweight. The purpose of this study was to determine the relationship of maternal nutritional status, birthweight and exclusive breastfeeding with the rate of stunting in Kedungrejo Village, Pakis District, Malang. This analytical observational study used a case–control design. The sample size of the case and control groups were 31 and 62 toddlers, respectively, selected using a purposive sampling technique. Data were analysed by Chi-square test. No significant relationship was seen between the maternal nutritional status and the rate of stunting (X2 value 0.151 < X 2 table 3.841), and the birthweight and the rate of stunting (X2 value 0.427 < X 2 table 3.841), however, there was a significant relationship between exclusive breastfeeding and the rate of stunting (X2 value 10.747 > X 2 table 3.841). Keywords: the birthweight of babies, exclusive breastfeeding, mother’s nutritional status, stunting